Students’ choice of postgraduate education at G University in Guangzhou, Guangdong Province, China: an in depth case-study - Liu, Dan (2016)
Previous studies of students’ higher education choices have been mainly examined in the US, European and Australian context, with few related empirical research studies in the context of China (Hemsley-Brown and Oplatka, 2015). Although there is no lack of various online surveys about the reasons driving students towards postgraduate education in China, little is known about how far their decisions were shaped by their specific circumstances which is the purpose of this study, which investigates the main factors influencing students’ decision-making about postgraduate education at G University in Guangzhou, Guangdong Province. To achieve this aim, three main research questions were asked: what motivated students to undertake PG education, why did they choose their particular subjects for PG studies, and why did they choose G University as their place of study? This study employs an-in depth case study approach. The research was conducted in two stages. In the first stage, questionnaires were distributed among the first-year postgraduate students at G University to get a general idea of what motivated them to undertake PG education and why they chose their particular subjects and place of study. In the second stage, 30 students who indicated their willingness in the questionnaires to participate in follow-up interviews were interviewed to explore the responses to the questionnaires in greater depth. The findings of this research were analysed from the theoretical aspects of human, cultural and social capital, as well as the related Chinese concept of guanxi. The findings indicated that students’ decisions to undertake PG education was mainly to enhance their employment competitiveness and to gain jobs with higher salaries and better advancement opportunities. In addition, the findings indicated that personal interest influenced either by their family's education or school teacher’s instruction constituted the main reason for choosing their specific fields of study. The findings also showed that family social capital and the social capital formed in the school context exerted great influence on students’ choices of postgraduate education. Further, students chose G University as their place of study mainly for its academic reputation, the quality of its faculties and resources, and its convenient location. The data indicated that students’ choices of postgraduate education were influenced by their individual economic, social and cultural backgrounds, or the interplay between human, cultural and social capital from the theoretical aspect. Enquiring into the students’ choices of postgraduate education in the specific Chinese social and cultural context contributes to the literature on students’ choices of higher education. It is hoped that the findings will provide some informed knowledge for students who plan to invest in their future employability through postgraduate education in China, as well as for the Chinese further and higher education system, which may gain a better understanding of its students and so be able to provide a better service to them.